Modelling the Impact of External Shocks on the Economy of Ukraine: DSGE Approach - Bazhenova, Olena; Bazhenova, Yuliya (Ekonomika, 2016)
The paper explores the dynamic stochastic general equilibrium model to study the impact of external shocks on the economy of Ukraine. The dynamic stochastic general equilibrium model is constructed for a small open economy that includes households, firms (domestic manufacturers and importers), government, the National Bank and external sector. The model assumes the new-Keynesian approach that includes the so-called “rigidities” of prices and wages, the existence of the households’ consumption habits and investments with adjustment costs. Also, it takes into account the country’s significant dependence on mineral products imports. All goods in the economy are divided into the domestic ones (that are exported and consumed in the country), imports and mineral products. So the purpose of the model is to study the impact of external shocks on the economy of Ukraine, such as a positive shock in world output, a positive shock in the world aggregate demand, a positive shock in the world interest rate, and a positive shock in world prices.
Keywords: DSGE model; small open economy; nominal rigidities; external sustainability; external economic shocks